A geosim analysis of ship resistance decomposition and scale effects with the aid of CFD. (November 2019) - Terziev, Momchil; Tezdogan, Tahsin; Incecik, Atilla
Highlights: A systematic geosim analysis is performed using CFD on the KCS. Ship resistance decomposition performed with the help of double body simulations. Scaling performed geometrically and by a change in the value of viscosity. Wave resistance is shown to vary with scale. Frictional resistance is shown to be influenced by the presence of a free surface. Abstract: Historically, the prediction ship resistance has received its fair share of attention by the scientific community. Yet, a robust scaling law still lacks, leaving testing facilities to rely on experience-based approaches and large datasets accumulated from years of operation. Academia's concern regarding this has not led to an extrapolation procedure, capable of bearing scrutiny adequately. One way to circumvent what has become the bane of the study of ship resistance is to perform Reynolds averaged Navier–Stokes (RANS) simulations directly in full-scale. The rapid advent of such methods has meant that confidence levels in predictions achieved by RANS simulations are low. This paper explores and demonstrates scale effects on the constituent components of ship resistance by performing a geosim analysis using a Computational Fluid Dynamics approach. Emphasis is placed on challenging the assumptions imposed as part of the currently accepted ship resistance extrapolation procedure. Our results suggest that a high degree of uncertainty exists in the calculated full-scale resistance depending on the approach taken towards its evaluation. In particular, scale effects are demonstrated in wave resistance, while free surface effects are palpable in the frictional resistance.